The Politics In Higher Education: The Contemporary Crises In Higher Education In Nigeria: A Consequence Of Fundamental Political Manipulations Of The Educational System (Military And Civilian Era) - Harry, Celestina Imade (Advances in Social Sciences Research Journal, 2020)
The Politics in Higher Education: The contemporary Crises in Higher Education in Nigeria is a consequence of fundamental political manipulations of the educational system – at both the federal and state levels. The government did not take the economy of the country into consideration. This had now made almost all the institutions of higher education of learning in Nigeria to face the financial constraints. For instance look at the specialized Universities of Agriculture at Abeokuta and Makurdi and the Faculties of Science and Technology in Nigerian universities are all facing the same financial problems as the Faculties of Arts and Social Sciences. Furthermore, libraries in most higher institutions of learning today are ill-equipped. Therefore, establishing higher institutions here and there without maintaining the already existing ones is not in the best interest for national development.